Recurrent Corneal Erosions in Corneal Dystrophies: a Review of the Pathogenesis, Differential Diagnosis, and Therapy - Omari, Amro A.; Mian, Shahzad I. (Klinische Monatsblätter für Augenheilkunde, 2018)
Introduction Recurrent corneal erosions in corneal dystrophies are visually significant and bothersome to patients. The goal of this article is to review the pathogenesis, differential diagnosis, and management of recurrent corneal erosions in corneal dystrophies.Patients and Methods Forty-eight articles and 1 textbook recently published on corneal erosions in corneal dystrophies were reviewed. The findings on the pathogenesis and clinical characteristics of erosions in each dystrophy were summarized. Any contradicting opinions for which the literature was unclear were either omitted or recorded as lacking strong evidence.Results and Conclusions The epithelial-stromal complex plays an important role in the pathogenesis of erosions in corneal dystrophies. The clinical features of each corneal dystrophy guide their diagnosis and management. A better understanding of the pathogenesis and clinical features of erosions in corneal dystrophies can lead to better clinical outcomes.
Keywords: recurrent corneal erosions; corneal dystrophy